A Multi‐institutional Analysis of Late Complications in Scapula, Fibula, and Osteocutaneous Radial Forearm Free Flaps. (29th January 2023) - Bollig, Craig A.; Walia, Amit; Pipkorn, Patrik J.; Jackson, Ryan S.; Puram, Sidharth V.; Rich, Jason T.; Paniello, Randy C.; Zevallos, Jose P.; Stevens, Madelyn N.; Wood, C. Burton; Rohde, Sarah L.; Sykes, Kevin; et al.
Abstract: Objectives: (1) Evaluate the association of flap type with late complications in patients undergoing osseous head and neck reconstruction with the fibula free flap (FFF), osteocutaneous radial forearm free flap (OCRFFF), and scapula free flap (SFF). (2) Compare the prevalence of late complications based on minimum duration of follow‐up. Study Design: Retrospective cohort study. Setting: Multiple academic medical centers. Methods: Patients undergoing FFF, OCRFFF, or SFF with ≥6‐month follow‐up were stratified by type of flap performed. The association of flap type with late complications was analyzed via univariable and multivariable logistic regression, controlling for relevant clinical risk factors. Additionally, the frequency of late complications by minimum duration of follow‐up was assessed. Results: A total of 617 patients were analyzed: 312 (50.6%) FFF, 230 (37.3%) OCRFFFF, and 75 (12.2%) SFF. As compared with the SFF, the FFF (adjusted odds ratio [aOR], 3.05; 95% CI, 1.61‐5.80) and OCRFFF (aOR, 2.17; 95% CI, 1.12‐4.22) were independently associated with greater odds of overall late recipient site wound complications. The SFF was independently associated with the lowest odds of hardware exposure when compared with the FFF (aOR, 2.61; 95% CI, 1.27‐5.41) and OCRFFF (aOR, 2.38; 95% CI, 1.11‐5.12). The frequency of late complications rose as minimum duration of follow‐up increased until plateauing at 36 months. Conclusions: This multi‐institutional study suggests that the long‐term complication profile of the SFF and OCRFFF compares favorably to the FFF. The SFF may be associated with the fewest overall late recipient site complications and hardware exposure, while the FFF may be associated with the most of these 3 options.